The efficacy of azithromycin and doxycycline for the treatment of rectal chlamydia infection: a systematic review and meta-analysis. (29th January 2015) - Kong, Fabian Yuh Shiong; Tabrizi, Sepehr N.; Fairley, Christopher Kincaid; Vodstrcil, Lenka A.; Huston, Wilhelmina M.; Chen, Marcus; Bradshaw, Catriona; Hocking, Jane S.
Abstract: Background: There are increasing concerns about treatment failure following treatment for rectal chlamydia with 1 g of azithromycin. A systematic review and meta-analysis was conducted to investigate the efficacy of 1 g of azithromycin as a single dose or 100 mg of doxycycline twice daily for 7 days for the treatment of rectal chlamydia. Methods: Medline, Embase, PubMed, Cochrane Controlled Trials Register, Australia New Zealand Clinical Trial Register and ClinicalTrials.gov were searched to the end of April 2014. Studies using 1 g of azithromycin or 7 days of doxycycline for the treatment of rectal chlamydia were eligible. Gender, diagnostic test, serovar, symptomatic status, other sexually transmitted infections, follow-up time, attrition and microbial cure were extracted. Meta-analysis was used to calculate pooled (i) azithromycin and doxycycline efficacy and (ii) efficacy difference. Results: All eight included studies were observational. The random-effects pooled efficacy for azithromycin (based on eight studies) was 82.9% (95% CI 76.0%–89.8%; I 2 = 71.0%; P < 0.01) and for doxycycline (based on five studies) was 99.6% (95% CI 98.6%–100%; I 2 = 0%; P = 0.571), resulting in a random-effects pooled efficacy difference (based on five studies) of 19.9% (95% CI 11.4%–28.3%; I 2 = 48.5%; P = 0.101) in favour of doxycycline. Conclusions: The efficacy of single-dose azithromycin may be considerably lower than 1 week of doxycycline for treating rectal chlamydia. However, the available evidence is very poor. Robust randomized controlled trials are urgently required.